Gamma Knife surgery for recurrent or persistent Cushing disease: long-term results and evaluation of biological effective dose in a series of 26 patients - Anne Balossier; Constantin Tuleasca; Christine Cortet-Rudelli; Gustavo Soto-Ares; Marc Levivier; Richard Assaker; Nicolas Reyns (Swiss Medical Weekly, 2021)
INTRODUCTION